2014
DOI: 10.1016/j.autneu.2013.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Moderate hyperhomocysteinemia provokes dysfunction of cardiovascular autonomic system and liver oxidative stress in rats

Abstract: Hyperhomocysteinemia (HHcy) is associated with cardiovascular disease, atherosclerosis and reactive oxygen species generation. Thus, our aim was to investigate whether there was an association between HHcy, blood pressure, autonomic control and liver oxidative stress. Male Wistar rats were divided into 2 groups and treated for 8weeks: one group (control, CO) received tap water, while the other group (methionine, ME) was given a 100mg/kg of methionine in water by gavage. Two catheters were implanted into the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…Hcy inhibits the activity of GSH in vitro and leads to a dramatic reduction of GSH. In conjunction with this reduction, other studies confirm that Hcy also significantly decreases the thiol redox state of vascular cells, as measured by the ratio of GSH/GSSG, through the oxidation of GSH . Superoxide dismutase is essential to catalyse the dismutation of superoxide and has been shown to protect cells from oxygen free radicals.…”
Section: Discussionmentioning
confidence: 78%
“…Hcy inhibits the activity of GSH in vitro and leads to a dramatic reduction of GSH. In conjunction with this reduction, other studies confirm that Hcy also significantly decreases the thiol redox state of vascular cells, as measured by the ratio of GSH/GSSG, through the oxidation of GSH . Superoxide dismutase is essential to catalyse the dismutation of superoxide and has been shown to protect cells from oxygen free radicals.…”
Section: Discussionmentioning
confidence: 78%
“…The pathological processes by which homocysteine promotes organ damage have yet not been fully elucidated. Oxidative stress [5] and activation of pro-inflammatory factors [6] have been proposed to explain the pathogenic effects of Hhcy. Previous studies have revealed that these processes induced by Hhcy were associated with initiation and progression of fibrosis characterized by an accumulation of extracellular matrix (ECM) proteins, particularly collagen and an imbalance of MMPs/TIMPs system, which also plays a determinant role in the regulation of collagen tissue turnover [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Disturbed fibrinogen levels may occur due to an established process of homocysteine vs proteins interactions. Recent studies have demonstrated that treatment with methionine for 8 weeks (100 mg/kg) led to liver dysfunction through increased ROS production [28].…”
Section: Discussionmentioning
confidence: 99%